Planning for innovation : through diáemination and utilization of knowledge - Havelock, R.G.; Guskin, A.; Frohman, M.; Havelock, M.; Hill, M.; Huber, J. (Michigan (EUA), 1971)
Sumario (En)
Ilus.; 150 ref.
Keywords: DIFUSION DE INFORMACION; INVESTIGACION; TRANSFERENCIA DE TECNOLOGIA; PROYECTOS DE DESARROLLO; CAPACITACION; TECNOLOGIA APROPIADA